2003
DOI: 10.1002/pmic.200300376
|View full text |Cite
|
Sign up to set email alerts
|

Improved proteome analysis of Saccharomyces cerevisiae mitochondria by free‐flow electrophoresis

Abstract: The analysis of complex cellular proteomes by means of two-dimensional gel electrophoresis (2-DE) is significantly limited by the power of resolution of this technique. Although subcellular fractionation can be a fundamental first step to increase resolution, it frequently leads to preparations contaminated with other cellular structures. Here, we chose mitochondria of Saccharomyces cerevisiae to demonstrate that an integrated zone-electrophoretic purification step (ZE), with a free-flow electrophoresis device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 30 publications
0
96
1
Order By: Relevance
“…A second possibility is that Fd-GOGAT is present in a subset of a heterogeneous mitochondrial population and that this Fd-GOGAT-containing subset is lost during FFE purification. For example, distinct yeast mitochondrial populations originating from different biological conditions or experimental manipulations can be resolved by FFE and as little as deletion of a single outer-membrane protein can yield a mitochondrial fraction of distinct mobility in FFE (Zischka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that Fd-GOGAT is present in a subset of a heterogeneous mitochondrial population and that this Fd-GOGAT-containing subset is lost during FFE purification. For example, distinct yeast mitochondrial populations originating from different biological conditions or experimental manipulations can be resolved by FFE and as little as deletion of a single outer-membrane protein can yield a mitochondrial fraction of distinct mobility in FFE (Zischka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The group of Lubman [23,24] developed a method for the fractionation of complex protein samples by a combination of IEF or chromatofocusing and RP-LC. Other groups have used alternative methods for prefractionation, such as CE, affinity chromatography, and ion-exchange chromatography [4,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The purity of organelles and other protein complexes is crucial to subcellular proteome research [13][14][15][16][17]. For the isolation of subcellular structures and organelles several methods, such as differential-and density-gradient centrifugation [18][19][20], immunoisolation [8], affinity purification, [21], and freeflow electrophoresis [22], have been applied. It has been shown that such fractionations improved identification of proteins from targeted subcellular structures [8,10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…3,7 μ-FFE's larger-scale, preparative counterpart has proven useful in separating a range of analytes, including cells, 8,9 cellular components, 10-14 and proteins. [15][16][17] In the near future, μ-FFE could be useful in analysis or micropreparative separations of the same analytes.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 μ-FFE's larger-scale, preparative counterpart has proven useful in separating a range of analytes, including cells, 8,9 cellular components, 10-14 and proteins. [15][16][17] In the near future, μ-FFE could be useful in analysis or micropreparative separations of the same analytes.Recently several researchers have investigated a variety of fabrication methods for μ-FFE devices to improve their performance. [4][5][6][18][19][20] In early designs two major problems were encountered.…”
mentioning
confidence: 99%